Subtitusi Tepung Cangkang Telur Ayam Sebagai Sumber Mineral Pakan Untuk Mengoptimalkan Produksi Ikan Nila (Oreochromis niloticus) - Syahrizal Syahrizal; Safratilofa Safratilofa; SRF Ayu Soraya (Universitas Batangahari Jambi, 2023)
This study aims to see the effect of eggshell flour as a mineral substitution in feed on optimizing tilapia production (Oreochromis. nilocitus). This experiment was conducted for 40 days using a Complete Randomized Design of 4 treatments and 3 repeats, with treatment of purebred chicken eggshell flour (TCTAR) and mineral mix. (MM) amounted to: (A. TCTAR 0.0%), and MM 5.0%), (B. TCTAR 2.0% and MM 3.0%), (C. TCTAR 4.0% and MM; 1%) and (D. TCTAR 5.0% and MM 0.0%). The best research results were average absolute growth in treatment C: 1.41 grams, for an average daily growth rate of 2.78%, and absolute length of 1.50 cm, followed by B: 2.75 grams, 1.34% and 1.31 cm, respectively; D: 2.64 grams, 1.21% and 1.28 cm; A: 2.49 grams, 1.08% and 1.12 cm. The best feed conversion ratio (FCR) is also C treatment 1.35% followed by B: 1.40%, D: 1.63% and A: 1.78%. Life quarters are different but not real B: 93.33%, C: 92.08, D: 91.25. Water quality supporting the environment in the normal range Temperature 27 - 28 0C, pH 6.8 - 7.7, DO 5.4 - 6.4 mg / L, CO2 5.4 - 9.1 mg / L and NH3 0.01 - 0.02 mg / L.